FOREWORD FROM HANDLING EDITOR - 10TH EDITION - Sodri, Ahyahudin (Journal of Environmental Science and Sustainable Development, 2023)
We are delighted to present the 10th edition of JESSD, published in July 2023. We have selected twelve of the best articles for this edition that related with topic of Environmental Science and Sustainable Development.